2022
DOI: 10.3390/curroncol29030130
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Smoking Cessation at 6 and 12 Months after a Clinical Tobacco Smoking Cessation Intervention in Head and Neck Cancer Patients in Northern Ontario, Canada

Abstract: Smoking during cancer treatment is associated with reduced treatment response and cancer recurrence in patients with tobacco-related cancers. The purpose of this study was to examine smoking characteristics in head and neck cancer patients (n = 503) with a history of smoking and examine the impact of an intensive clinical tobacco intervention to patients who were currently smoking. All participants completed an interviewer-administered questionnaire at study enrollment which examined smoking behaviours, motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In this review, evidence identified significant barriers for healthcare professionals supporting smokers with cancer due to a lack of confidence and perceptions [ 39 ]. The findings in this review are consistent with Feuer’s [ 55 ] review of 29 studies that examined smoking relapse for a population who are cancer survivors. They suggest that smoking cessation after a cancer diagnosis is understudied, and that interpretation of interventions is challenging due to heterogeneity (p. 102237).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this review, evidence identified significant barriers for healthcare professionals supporting smokers with cancer due to a lack of confidence and perceptions [ 39 ]. The findings in this review are consistent with Feuer’s [ 55 ] review of 29 studies that examined smoking relapse for a population who are cancer survivors. They suggest that smoking cessation after a cancer diagnosis is understudied, and that interpretation of interventions is challenging due to heterogeneity (p. 102237).…”
Section: Discussionsupporting
confidence: 89%
“…It is crucial to consider the longevity of support that may be needed beyond the usual eight or 12-week programme. Santi et al [ 55 ] confirm the challenges for those quitting and the potential for additional support beyond six months, as noted in the updated National Institute for Health and Care Excellence (NICE) guidelines [ 57 ]. Evidence indicates the importance of married/partnered patients for social support when quitting [ 53 ].…”
Section: Discussionmentioning
confidence: 94%
“…This is a similar conclusion to that of our study ( Table 3 ), in which the risk of hip fracture did not significantly decrease even among smokers within 2 years. Another study found that approximately 60% of quitters resumed smoking within 6 to 12 months [ 41 ]. It is possible that some of the short-term quitters in our study resumed smoking during the follow-up period, diluting the positive effects of 2 years of abstinence on hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the Northeast Cancer Centre, which offers an intensive clinical tobacco intervention involving multiple follow-up appointments and pharmacotherapy. A study of head and neck cancer patients found that, although these patients reported high levels of nicotine dependence, many were able to successfully quit [ 11 ].…”
Section: Introductionmentioning
confidence: 99%